Археологічні дослідження Цареборисівської фортеці у 2008 р. - Голубєва, І.В. (Археологічні дослідження в Україні, 2009)
The article presents a concise description of the results of planned archaeological research in the Fortress of Tsar Borys in 2008. During the excavations a public square has been localized. The materials obtained corroborated the conclusion that local elite resided in dytynets (citadel).